Behaviour of toxic metabolites of the insecticide 14C- dissulfoton in beans and soils - Andréa, Mara M. de; Wiendl, Frederico M.; Rüegg, Elza F. (Pesquisa Agropecuaria Brasileira, 2014)
The absorption, translocation, and degradation of three toxic metabolites - probably sulfoxide, oxon sulfoxide and sulfone - of the insecticide 14C-disulfoton applied in three types of Brazilian soils were studied in bean (Phaseolus vulgaris L) seedlings and soils. The compounds were extracted from soils and seedlings with organic solvente, and quantified by the liquid scintillation system. The organic extracts were thin-layer chromatographed and autoradiographed for visualization of the compounds. Seedlings and soils were also submitted to wet combustion to determine the bound residues. In the soils, the compounds did almost not dissipate, although the plante metabolized rapidly the absorbed compounds. The amount of bound residues increased in the soils with time, and showed some relation with the organic malter content. It seems that the hazard of environmental contamination due to plant residues does not exist. However, the compounds can remain in the soils and pollute the edaphic environment.